Problematika Hasil Belajar Matematika Pada Pembelajaran Tatap Muka Terbatas Pandemi Covid-19 Ditinjau Dari Lingkungan Belajar - Fauziah, Yesi Ulfah; Ratnaningsih, Nani Ratnaningsih (Mandalika Mathematics and Educations Journal, 2021)
The aim of this research is to know about the problematic of the students’ learning outcome in limited directly learning at the covid-19 pandemic which looked by the learning environment. This research is descriptive method with qualitative approach. The subjects of this research are 4 students in 9th grade at SMP Terpadu Miftahul Khoir which have high and low ability. 2 students live in Islamic Boarding School, and 2 students don’t live in it. The test appropriates to cognitive Taxonomy Bloom Revise. The technique to take the sample is Purposive sampling. The instruments of this research are mathematic test, questionnaire, and interview. The techniques of data analysis are data reduction, data presentation, and conclusion. The result of this research is the students cannot use the facility well. The students which have high ability can achieve the indicator of understanding and applying, but cannot know how to finish the non-routine exercises. And the low ability students cannot finish the understanding and applying indicator exercises.